2017
DOI: 10.1007/s00414-017-1721-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of pulmonary edema in forensic autopsy cases of fatal anaphylactic shock using Fourier transform infrared microspectroscopy

Abstract: Anaphylaxis is a rapid allergic reaction that may cause sudden death. Currently, postmortem diagnosis of anaphylactic shock is sometimes difficult and often achieved through exclusion. The aim of our study was to investigate whether Fourier transform infrared (FTIR) microspectroscopy combined with pattern recognition methods would be complementary to traditional methods and provide a more accurate postmortem diagnosis of fatal anaphylactic shock. First, the results of spectral peak area analysis showed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…Nevertheless, our FTIR-based results show that the biochemical profiles of fatal hypothermic, fatal hyperthermic and normothermic hypothalamus tissues were significantly different. This study, supported by our previous studies [89,90], demonstrates that some tissues or organs regarded as nonspecific for the determination of the cause of death in forensic pathology do indeed have specific biochemical fingerprints. There is a high potential for this technique to augment the results of conventional forensic post-mortem examination and provide for a more accurate determination of the cause of death.…”
Section: Resultssupporting
confidence: 87%
“…Nevertheless, our FTIR-based results show that the biochemical profiles of fatal hypothermic, fatal hyperthermic and normothermic hypothalamus tissues were significantly different. This study, supported by our previous studies [89,90], demonstrates that some tissues or organs regarded as nonspecific for the determination of the cause of death in forensic pathology do indeed have specific biochemical fingerprints. There is a high potential for this technique to augment the results of conventional forensic post-mortem examination and provide for a more accurate determination of the cause of death.…”
Section: Resultssupporting
confidence: 87%
“…The model demonstrated a satisfactory discrimination between the FAS cases and other cases included in the study. This proof of concept study highlighted the potential use of ATR-FTIR in the postmortem diagnosis of FAS [132].…”
Section: Postmortem Diagnosis Of Other Ambiguous Death Causesmentioning
confidence: 78%
“…The use of ATR-FTIR in the postmortem diagnosis of ambiguous death causes, such as fatal anaphylactic shock (FAS) and diabetic ketoacidosis (DKA), has been explored in a few studies [132,133]. FAS is a severe systemic syndrome triggered by allergic reaction to some foods, drugs, or venoms.…”
Section: Postmortem Diagnosis Of Other Ambiguous Death Causesmentioning
confidence: 99%
“…Pulmonary edema fluid is usually considered to be nonspecific biological evidence regarding the cause of death determination in forensic autopsies because it is ubiquitous in forensic histopathological analysis. In fact, several studies have demonstrated that pulmonary edema fluid associated with different causes of death involves different specific biochemical and mRNA expression patterns . Unlike blood serum, one of the most common samples for biochemical and toxical tests in forensic investigations and that can easily be contaminated by the visible blood composition, pulmonary edema fluid is stored in the alveolar space and protected by the alveolar wall, which acts as a screen that excludes the visible blood composition (see Figure 3A).…”
Section: Resultsmentioning
confidence: 99%